Dynamic multiphoton imaging of acellular dermal matrix scaffolds seeded with mesenchymal stem cells in diabetic wound healing. Issue 7 (6th May 2018) - Chu, Jing; Shi, Panpan; Deng, Xiaoyuan; Jin, Ying; Liu, Hao; Chen, Maosheng; Han, Xue; Liu, Hanping
Abstract : Significantly effective therapies need to be developed for chronic nonhealing diabetic wounds. In this work, the topical transplantation of mesenchymal stem cell (MSC) seeded on an acellular dermal matrix (ADM) scaffold is proposed as a novel therapeutic strategy for diabetic cutaneous wound healing. GFP‐labeled MSCs were cocultured with an ADM scaffold that was decellularized from normal mouse skin. These cultures were subsequently transplanted as a whole into the full‐thickness cutaneous wound site in streptozotocin‐induced diabetic mice. Wounds treated with MSC‐ADM demonstrated an increased percentage of wound closure. The treatment of MSC‐ADM also greatly increased angiogenesis and rapidly completed the reepithelialization of newly formed skin on diabetic mice. More importantly, multiphoton microscopy was used for the intravital and dynamic monitoring of collagen type I (Col‐I) fibers synthesis via second harmonic generation imaging. The synthesis of Col‐I fibers during diabetic wound healing is of great significance for revealing wound repair mechanisms. In addition, the activity of GFP‐labeled MSCs during wound healing was simultaneously traced via two‐photon excitation fluorescence imaging. Our research offers a novel advanced nonlinear optical imaging method for monitoring the diabetic wound healing process while the ADM and MSCs interact in situ. Schematic of dynamic imaging of ADM scaffolds seeded with mesenchymal stem cells in diabetic wound healing using multiphoton microscopy. PMT, photo‐multiplier tube. Abstract : The intravital monitoring of the activity of acellular dermal matrix (ADM) scaffolds seeded with GFP‐labeled MSCs during diabetic wound healing via two‐photon excitation fluorescence imaging. In addition, the dynamic synthesis of collagen type I fibers was simultaneously traced by second harmonic generation imaging. Multiphoton microscopy with a novel nonlinear optical imaging was used for monitoring the diabetic wound healing process while the ADM and MSCs interact in situ.